Outcomes of patients with a pretransplant history of early-stage melanoma. Issue 5 (October 2018) - Puza, Charles J.; Barbas, Andrew S.; Mosca, Paul J.
Abstract : A history of melanoma within the preceding 5 years is commonly considered a contraindication to solid organ transplantation. We investigated how a pretransplant history of melanoma impacts patient survival and melanoma recurrence. Institutional Review Board approval was obtained, and Duke's retrospective database was used to identify 4552 patients who underwent a solid organ transplant at Duke University from 1 January 2001 to 31 December 2016. Data with regard to the transplant, melanoma characteristics, rejection episodes, and survival were recorded. Of 4552 patients who underwent a solid organ transplant, 12 (0.3%) had a history of melanoma before transplant (six with melanoma in situ and six with stage I disease). The median time between melanoma diagnosis and transplant was 4.13 years (range: 1.1–13.3 years). The study cohort consisted of four liver transplants, four lung transplants, one kidney transplant, one heart transplant, one small bowel transplant, and one multivisceral transplant. At the median follow-up time of 2.8 years, 10 (83.3%) patients were alive. In nonmelanoma cohorts, the 3-year survival is 70% for thoracic transplants, 78% for liver transplants, and 88% for kidney transplants. In well-selected patients with a history of early-stage melanoma and an appropriate time interval between melanoma treatment and transplant, post-transplant outcomes are favorable.